2001
DOI: 10.1148/radiology.219.3.r01jn34793
|View full text |Cite
|
Sign up to set email alerts
|

Nonpalpable Breast Cancer: Percutaneous Diagnosis with 11- and 8-gauge Stereotactic Vacuum-assisted Biopsy Devices

Abstract: This study demonstrated no difference in breast cancer diagnosis with the 8- and 11-gauge SVAB systems, but the accuracy of breast cancer diagnosis was greater in lesions smaller than 30 mm than in larger lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 20 publications
6
31
1
2
Order By: Relevance
“…Although SVAB allows more accurate histopathologic results, underestimation still occurs (7,10,18). Some investigators have found rates of underestimation ranging from 5% to 29% for DCIS at SVAB (6,9,(11)(12)(13). In this study, the underestimation rate of DCIS was 18%.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Although SVAB allows more accurate histopathologic results, underestimation still occurs (7,10,18). Some investigators have found rates of underestimation ranging from 5% to 29% for DCIS at SVAB (6,9,(11)(12)(13). In this study, the underestimation rate of DCIS was 18%.…”
Section: Discussionmentioning
confidence: 50%
“…However Laurenco et al (13) found a statistically significant relation between the increasing size and underestimation rates. Brem et al (6) found the underestimation rates to be significantly higher in lesions 30 mm or larger. Orsaria et al (16) reported that lesions larger than 40 mm have a greater probability of having invasive components than others.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations